2021
DOI: 10.1111/codi.15845
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of C‐reactive protein, procalcitonin and neutrophils for the early detection of anastomotic leakage after colorectal resection: a multicentric, prospective study

Abstract: Aim The aim was to determine the accuracy of C‐reactive protein (CRP), procalcitonin and neutrophils in the early detection (fourth postoperative day) of anastomotic leakage (AL) after colorectal surgery. Methods We conducted a multicentre, prospective study that included a consecutive series of patients who underwent colorectal resection with anastomosis without ostomy (September 2015 to December 2017). CRP, procalcitonin and neutrophil values on the fourth postoperative day after colorectal resection along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…9 Recently, CRP has been widely reported as an early predictor of postoperative complications, such as anastomotic leakage, after colorectal surgery. [11][12][13][14][15][16][17] Sala et al conducted a multicenter prospective study involving 2,501 cases undergoing colorectal surgery and concluded that CRP is a reliable marker for detecting leakage, with a cutoff level of 11.9 mg/dL on POD 4, a sensitivity of 70%, a specificity of 81%, and an NPV of 97%. 11 Yeung et al conducted a systematic review involving 6,647 cases undergoing colorectal surgery and found a significant difference in the CRP values on POD 1 to POD 7 between the leaked and nonleak groups, particularly on POD 4 to POD 7, with a specificity of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Recently, CRP has been widely reported as an early predictor of postoperative complications, such as anastomotic leakage, after colorectal surgery. [11][12][13][14][15][16][17] Sala et al conducted a multicenter prospective study involving 2,501 cases undergoing colorectal surgery and concluded that CRP is a reliable marker for detecting leakage, with a cutoff level of 11.9 mg/dL on POD 4, a sensitivity of 70%, a specificity of 81%, and an NPV of 97%. 11 Yeung et al conducted a systematic review involving 6,647 cases undergoing colorectal surgery and found a significant difference in the CRP values on POD 1 to POD 7 between the leaked and nonleak groups, particularly on POD 4 to POD 7, with a specificity of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Sala et al conducted a multicenter prospective study involving 2,501 cases undergoing colorectal surgery and concluded that CRP is a reliable marker for detecting leakage, with a cutoff level of 11.9 mg/dL on POD 4, a sensitivity of 70%, a specificity of 81%, and an NPV of 97%. 11 Yeung et al conducted a systematic review involving 6,647 cases undergoing colorectal surgery and found a significant difference in the CRP values on POD 1 to POD 7 between the leaked and nonleak groups, particularly on POD 4 to POD 7, with a specificity of 100%. 12 Although these reports were in the field of colorectal surgery, oropharyngeal surgery is classified as class II/clean-contaminated operative wound according to the Centers for Disease Control and Prevention criteria similar to colorectal surgery; therefore, CRP can be applied as a predictor of postoperative leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A multicenter prospective study showed that the detection of CRP on the fourth postoperative day of CRC could improve the accuracy of AL diagnosis compared to PCT or neutrophil count, and a high negative predictive value of CRP could guide the safe discharge time of patients. 30 In addition, combined detection of CRP trajectory and cut-off points may be also valuable in accurate diagnosis of AL. 31 Apart from detecting blood inflammation indicators, a recent study suggested that high bacteriological concentration in drainage fluid was a reliable indicator for the prediction and diagnosis of AL.…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…Several independent factors have been identi ed, including distance of the tumor from anal verge, age, male gender and obesity [5][6][7]. Moreover, many recent studies have proposed in ammatory markers as early predictors of leakage-related infection [8][9][10]. Unfortunately, retrospective and observational studies are greatly limited by nonstandard data records.…”
Section: Introductionmentioning
confidence: 99%